Macroevolution of thermal tolerance in intertidal crabs from Neotropical provinces: A phylogenetic comparative evaluation of critical limits. Issue 9 (31st March 2017) - Faria, Samuel C.; Faleiros, Rogério O.; Brayner, Fábio A.; Alves, Luiz C.; Bianchini, Adalto; Romero, Carolina; Buranelli, Raquel C.; Mantelatto, Fernando L.; McNamara, John C.
Abstract: Thermal tolerance underpins most biogeographical patterns in ectothermic animals. Macroevolutionary patterns of thermal limits have been historically evaluated, but a role for the phylogenetic component in physiological variation has been neglected. Three marine zoogeographical provinces are recognized throughout the Neotropical region based on mean seawater temperature ( T m ): the Brazilian ( T m  = 26 °C), Argentinian ( T m  = 15 °C), and Magellanic ( T m  = 9 °C) provinces. Microhabitat temperature (MHT) was measured, and the upper (UL50 ) and lower (LL50 ) critical thermal limits were established for 12 eubrachyuran crab species from intertidal zones within these three provinces. A molecular phylogenetic analysis was performed by maximum likelihood using the 16S mitochondrial gene, also considering other representative species to enable comparative evaluations. We tested for: (1) phylogenetic pattern of MHT, UL50, and LL50 ; (2) effect of zoogeographical province on the evolution of both limits; and (3) evolutionary correlation between MHT and thermal limits. MHT and UL50 showed strong phylogenetic signal at the species level while LL50 was unrelated to phylogeny, suggesting a more plastic evolution. Province seems to have affected the evolution of thermal tolerance, and only UL50 was dependent on MHT. UL50 was similar between the two northern provinces compared to the southernmost while LL50 differed markedly among provinces. Apparently, critical limits are subject to different environmental pressures and thus manifest unique evolutionary histories. An asymmetrical macroevolutionary scenario for eubrachyuran thermal tolerance seems likely, as the critical thermal limits are differentially inherited and environmentally driven. Abstract : This investigation retrieves the evolutionary history of thermal tolerance in eubrachyuran crabs distributed throughout the biogeographical provinces of the Neotropical region, from northern Brazil to subantarctic Patagonia. Using phylogenetic comparative methods, we tested for: (1) phylogenetic pattern in microhabitat temperature (MHT), and upper (UL50 ) and lower (LL50 ) critical thermal limits; (2) effect of thermal province on the evolution of both limits; and (3) evolutionary correlation between MHT and thermal limits. The macroevolutionary scenario for eubrachyuran thermal tolerance seems to be asymmetrical, as the critical thermal limits are both inherited and environmentally driven to different degrees. Photograph shows a male fiddler crab, Uca maracoani, from the Brazilian zoogeographical province (kindly provided by Prof. Carl Leo Thurman, University of Northern Iowa, USA).